Universals in Learning to Read Across Languages and Writing Systems - Verhoeven, Ludo; Perfetti, Charles (Scientific studies of reading, 2022)
In this article, we provide a cross-linguistic perspective on the universals and particulars in learning to read across seventeen different orthographies. Starting from the assumption that reading reflects a learned sensitivity to the systematic relationships between the surface forms of words and their meanings, we chose a broad group of seventeen languages, representing syllabic, morphosyllabic, alphasyllabic (abugida), abjad, and alphabetic writing systems. We investigated the systematic variation among these languages in their written forms and in their mapping of writing units to language units, and demonstrated the universality of operating principles in learning to read across languages and writing systems.